An Empirical Study Examining an Extended TAM Model in the Context of a Facebook Event Page - Phuong , Tran Thi Kim; Vinh , Tran Trung (Asian Journal of Empirical Research, 2019)
This study provides a deeper understanding of the inner-mechanism which users engage in their acceptance of social media (in this case, Facebook event pages) via extending the TAM model by adding three factors: emotion, perceived enjoyment and perceived relevance. This work applied structural equation modelling (SEM) to test 13 hypotheses, with collected data from 323 Facebook users who have been members of the event page “Traveling Talent 2017”. Empirical results showed that the model fits well with the sample. The results of empirical tests using a structural equation model confirm all the research hypotheses. Implications and insights are given for event practitioners and are discussed accordingly.